Polechina I.S. Mechanisms of promoting socio-cultural complex corporate culture of public administration in Ukraine - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The mechanisms of development of socio-cultural component of corporate culture in public administration are considered. The essence of organizational-legal and socio-psychological mechanisms of corporate culture is explored